PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA JUDI TOGEL BERDASARKAN KITAB UNDANG-UNDANG HUKUM PIDANA DI WILAYAH HUKUM KEPOLISIAN RESOR KAMPAR - Hamdan '; Syaifullah Yophi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Kampar adistrictin the city dubbed the porch mecca, butthe nicknameis juststay porch mecca name alone, whichhas beendam agedbythe community withactionsor adverseactions that are contrary tolawand religious norms. one of the formsof these adverseperbutanisgambling, various forms ofgambling, (kiw-kiw, song, cockfighting, toggle etc.), writing this essay, namely; First Kampar Knowin gand understanding the implementation of law enforcemen tagainst criminal acts gambling toggle based onthe Code of Criminal Policein thearea of Kampar Both Knowin gandunder standing the factor sinhibiting the implementation of law enforcementagainstcriminal actsgambling togglebased onCode ofCriminal Lawin Police Kampar region. Third, Knowingandunder standing theef fortto overcomethe obstaclesin the implementation oflaw enforcemen tagainst criminal acts gambling toggle based onthe Code of Criminal Policein thearea of Kampar. This type of researchis classified intotypes ofsociologicalresearch, ieresearch on theeffectiveness of the lawin force, the nature ofthisresearchisdescriptive research thatdescribesystematicallythe facts andcharacteristics ofthe object under study appropriately.From the research, there arethree main problem sthatcan beinferred. First, law enforcemen tagainst criminal acts gambling lottery jurisdiction sKampar Policeconductedlaw enforcemen tpreventiveand repressive law enforcement. Secondly, Constraints facedin theenforcement ofcriminal lawgambling toggle. AdviceAuthor, First, Kampar Police Shouldbeworking hardagainin oreradicatethe crime of lottery gamblingin the communityso thatthe community teci safe, peaceful, serene andrealization backporch meccadistrict. second, Kampar Police shouldbecloser tothe peopleso thatthe information submittedwell receivedthatcan be interconnected witheach other informed. Thirdly, For the people ofKampar Regencyin order notto cover upanylotterygamblingactionoccurs, ifthe gambling actstill continuesto eimmediately reportedto the police, the crime of gambling togglethatcan beeradicatedthroughthe roots.